2019
DOI: 10.1587/transinf.2018ntp0016
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target Classification Based Automatic Virtual Resource Allocation Scheme

Abstract: In this paper, we propose a method for automatic virtual resource allocation by using a multi-target classification-based scheme (MTCAS). In our method, an Infrastructure Provider (InP) bundles its CPU, memory, storage, and bandwidth resources as Network Elements (NEs) and categorizes them into several types in accordance to their function, capabilities, location, energy consumption, price, etc. MTCAS is used by the InP to optimally allocate a set of NEs to a Virtual Network Operator (VNO). Such NEs will be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For each figure, each row corresponds to the binary classification model of one class label. The first third of the columns correspond to the discrete version of kNN-augmented features in (10), the middle third of the columns to the continuous version of kNN-augmented features in (11), and the last third of the columns to the maximum margin-augmented features in (12). It is shown that, for each third of all columns, the diagonal element usually takes the largest value in its corresponding row.…”
Section: Further Analysis 1) Effectiveness Of Algorithmic Designmentioning
confidence: 99%
“…For each figure, each row corresponds to the binary classification model of one class label. The first third of the columns correspond to the discrete version of kNN-augmented features in (10), the middle third of the columns to the continuous version of kNN-augmented features in (11), and the last third of the columns to the maximum margin-augmented features in (12). It is shown that, for each third of all columns, the diagonal element usually takes the largest value in its corresponding row.…”
Section: Further Analysis 1) Effectiveness Of Algorithmic Designmentioning
confidence: 99%
“…Firstly, q 2 first-level classifiers are trained (steps 1-6). Then, training sets which will be used to train the second-level classifiers are constructed (steps [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. After that, the second-level classifier for each class space is induced one by one (steps [23][24][25].…”
Section: The Seem Approachmentioning
confidence: 99%
“…Here, each class variable corresponds to one specific class space which characterizes the object's semantics from one dimension. Multi-dimensional classification (MDC) techniques have been widely utilized in real-world applications involving objects with rich semantics [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…), and from the scenario dimension (with possible classes wedding, memorial, saloon, etc.). Such kinds of applications widely exist in computer vision [3][4][5][6][7][8][9], text mining [10][11][12][13][14], bioinformatics [15][16][17][18][19][20][21], ecology [22,23], and beyond [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%